Carbon Cloth Supported Nano-Mg(OH)2 for the Enrichment and Recovery of Rare Earth Element Eu(III) From Aqueous Solution - Li, Yinong; Tian, Chen; Liu, Weizhen; Xu, Si; Xu, Yunyun; Cui, Rongxin; Lin, Zhang (Frontiers in Chemistry, 2018)
Nano-Mg(OH)2 is attracting great attention as adsorbent for pre-concentration and recovery of rare earth elements (REEs) from low-concentration solution, due to its superior removal efficiency for REEs and environmental friendliness. However, the nanoparticles also cause some severe problems during application, including aggregation, blockage in fixed-bed column, as well as the difficulties in separation and reuse. Herein, in order to avoid the mentioned problems, a carbon cloth (CC) supported nano-Mg(OH)2 (nano-Mg(OH)2@CC) was synthesized by electrodeposition. The X-ray diffraction and scanning electron microscopy analysis demonstrated that the interlaced nano-sheet of Mg(OH)2 grew firmly and uniformly on the surface of carbon cloth fibers. Batch adsorption experiments of Eu(III) indicated that the nano-Mg(OH)2@CC composite maintained the excellent adsorption performance of nano-Mg(OH)2 toward Eu(III). After adsorption, the Eu containing composite was calcined under nitrogen atmosphere. The content of Eu2O3 in the calcined material was as high as 99.66%. Fixed-bed column experiments indicated that no blockage for Mg(OH)2@CC composite was observed during the treatment, while the complete blockage of occurred to nano-Mg(OH)2 at an effluent volume of 240 mL. Moreover, the removal efficiency of Mg(OH)2@CC was still higher than 90% until 4200 mL of effluent volume. This work provides a promising method for feasible application of nanoadsorbents in fixed-bed process to recycle low-concentration REEs from wastewater.